Potret Sosial Pulau Barrang Lompo: Analisis Karakteristik Masyarakat Lokal dan Pendatang Berdasarkan Daerah Asal Mata Pencaharian, Ras, Bahasa, Suku, Kepercayaan, dan Demografi - Rahim, Anayah Amelinda; Sari, Inez Veronika; Syamsinar, Syamsinar; Mappe, Ulfa Utami (Program Studi Sosiologi, 2025)
Social change and population mobility in coastal areas have created complex interaction dynamics between local and migrant communities, making Barrang Lompo Island an important micro-representation of Indonesia's coastal multiculturalism. This study aims to identify and analyze the social characteristics of local and migrant communities based on regional origin, livelihoods, ethnicity, language, beliefs, and demographic conditions. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation, and analyzed thematically. The results showed that there is a social division between local people who have high emotional attachment to the island and migrants who come with economic or marriage motivations. Despite different ethnic and linguistic backgrounds, both groups are able to establish harmonious social interactions through the use of the Makassar language and the common religion of Islam as social glue. The findings contribute to the understanding of social integration processes in multiethnic coastal communities and suggest the need for social development policies.